Magnetically separable single-site Ti-Fe3O4@MCM-41 catalyst for selective epoxidation of olefins - Jha, Ajay; Patil, Chetana R.; Garade, Ajit C.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2013)
Magnetically separable Ti-Fe3O4@MCM-41 (Ti-MS) catalysts were prepared by postgrafting Ti with varying loading on mesoporous silica containing dispersed magnetite. The hexagonal structure of Ti-MS catalysts with a periodicity in the pores and a highly ordered hexagonal matrix was established by X-ray diffraction and transmission electron microscopy, while diffuse reflectance UV showed the isolated tetrahedral Ti species coordinated with O2-. From the Fourier transform infrared studies, the extent of Ti-O-Si linkage was found to increase with increase in Ti-loading from 1 to 5 wt %beyond which (10%), the intensity of Ti-O-Si band decreased due to the polymerization of the Ti on the silica surface. Silanol groups on the surface of silica interact with the precursor Ti((OPr)-Pr-i)(4) to give site isolated tetrahedral Ti-species responsible for complete selectivity to the epoxide in the epoxidation of cyclooctene. The magnetic property facilitated easy recovery of the catalyst for its successful eight recycles showing its stability under reaction conditions.

Selective production of furanic ethers from lignocellulosic biomass over mesoporous Zr-incorporated SBA-15 catalyst - Patil, Chetana R.; Rode, Chandrashekhar, V. (ChemistrySelect, 2018)
Etherification of furanic compounds such as furfuryl alcohol (FA) and 5-(Hydroxymethyl) furfural (5-HMF) to the corresponding ethers was successfully achieved over Zr-SBA-15 catalyst. For this purpose, various Zr-SBA-15 catalysts with different Zr/Si molar ratios in self-generated acidic environment were prepared by one-pot strategy in self-generated acidic environment. XRD analysis revealed the increase in the d-spacing from 9.021 nm for parent SBA-15 to 11.66 nm for Zr-SBA-15, confirming the incorporation of Zr into the framework without disturbing the mesoporous structure of SBA-15. For the lowest Zr concentration of 0.09 M, hexagonally ordered porous structure was found to be retained as confirmed by TEM while, increase in Zr/Si molar ratio to 0.14, resulted in loss of long range order mesoporosity. The presence of both Lewis and Bronsted acid sites in Zr-SBA-15 catalyst as evidenced by py-IR, were due to the introduction of Zr in the frame work of SBA-15. The co-existence of Lewis and Bronsted acid sites in Zr-SBA-15 was responsible to catalyze etherification of FA and esterification of levulinic acid producing 2-(Ethoxymethyl) furan and ethyl levulinate selectively, both of which are bio-derived fuel additives.

Synthesis of diesel additives from fructose over PWA/SBA-15 catalyst - Patil, Chetana R. (Fuel, 2018)
A series of composites of phosphotungstic acid (PWA) H3PW12O40 with SBA-15 were prepared by varying PWA amount from 5% to 30% by one-step sol-gel hydrothermal as well as by impregnation methods. Successful incorporation of PWA into the SBA-15 framework by sol-gel method was confirmed by 31P NMR in which a shifting of the peak due to tetrahedral ‘P’ atom of PWA from −14.32 and −14.49 ppm was observed. The composites exhibited both Brønsted and Lewis acidity, large and well distributed three dimensional interconnected pores with high surface areas exhibiting excellent activity for one pot synthesis of 5-(hydroxymethyl) furfural (5-HMF) and 5-(ethoxymethyl) furfural (EMF) from fructose. The minimum loading of 5% of PWA in SBA-15, gave 78% fructose conversion with the highest yield of 70% towards 5-HMF. Increase in PWA loading up to 20% resulted in the enhanced fructose conversion of 95% accompanied by further etherification of 5-HMF to 67 and 12% yield towards EMF and ethyl levulinate (EL), respectively. Increasing the % of PWA in SBA-15 matrix resulted in increase in the acidity of the composites giving the yield trend as 5-HMF < EMF < EL. Catalyst prepared by sol-gel method showed excellent recyclability up to 3 reuses
Keywords: 5-(Ethoxymethyl) furfural; 5-(Hydroxymethyl) furfural; Phosphotungstic acid; SBA-15

Cooperative acid-base sites of solid Ba-Zr mixed oxide catalyst for efficient isomerization of glucose to fructose in aqueous medium - Shaikh, Samrin S.; Patil, Chetana R.; Kondawar, Sharda E.; Rode, Chandrashekhar V. (ChemistrySelect, 2020)
Efficient and highly selective isomerization of glucose to fructose was achieved by using the inexpensive Ba-Zr mixed metal oxide catalyst. Catalyst was prepared by varying Ba-Zr ratios using co-precipitation method. Various phases formed, planes exposed, morphology, elemental composition and particle size, basic site density and strength, oxidation state of elements were well studied by using various characterization techniques. The XRD analysis clearly indicates the presence of Ba+2 and Zr+4 in the form of BaO, ZrO2 and BaZrO3 phases. The SEM and HR-TEM images indicate that, Ba-Zr (2 : 1) catalyst prepared showed uniform morphology with spherical and rod-shaped particles ranging from 300 to 600 nm. Under the optimized reaction conditions Ba-Zr (2 : 1) catalyst exhibited excellent results in terms of 57 % of glucose conversion with 89 % selective formation of glucose. The presence of both acidic as well as basic sites play vital roles in activating the substrate molecules to selectively yield fructose. Ba-Zr (2 : 1) catalyst showed excellent recyclability performance up to four recycles.
Keywords: Co-precipitation; fructose; glucose; isomerization; mixed metal oxide

Single-pot alcoholysis of furfuryl alcohol to alkyl levulinates using heterogenized p-TSA catalyst** - Patil, Chetana R.; Kamble, Sanjay P.; Rode, Chandrashekhar V. (ChemistrySelect, 2021)
Synthesis of levulinate esters which are known to be excellent sustainable fuel additives, was achieved by alcoholysis of furfuryl alcohol over strong solid acid catalyst, prepared by copolymerization of p-toluenesulfonic acid with paraformaldehyde. Our catalyst possessed Bronsted acidity (3 mmol/g) with an excellent stability up to 220 degrees C. XPS, FT-IR and Pyridine-IR along with microanalysis studies confirmed the presence of terminal -SO3H functional groups responsible for Bronsted acidity in the catalyst. The catalyst was found to efficiently catalyze the alcoholysis of furfuryl alcohol to give alkyl levulinates under mild reaction conditions. The complete conversion of furfuryl alcohol with 96 % and 97 % selectivities to ethyl and butyl levulinates could be achieved using ethanol and butanol, respectively. Detailed study on effect of various reaction parameters like catalyst loading, reaction time and reaction temperature on conversion and product distribution was also carried out for the ethanolysis of furfuryl alcohol to ethyl levulinate. The catalyst could be easily recovered and recycled for five times successfully, with no loss in its original activity.
Keywords: Biomass; ethyl levulinate; Fuel additive; Furfuryl alcohol; heterogeneous catalysis

Enhanced anisole hydroxylation over a hierarchical micro/mesoporous TS-1 catalyst - Patil, Chetana R.; Niphadkar, Prashant; Kamble, Sanjay P.; Rode, V. Chandrashekhar (New Journal of Chemistry, 2022)
Hierarchical TS-1 materials were synthesized using hydrothermal synthesis and a post modification technique through desilication. They were evaluated for hydroxylation of anisole to produce industrially important chemicals, o-methoxyphenol (OMP) and p-methoxyphenol (PMP). The detailed characterization of the prepared catalysts, such as morphology, structure, nature of Ti and surface area were obtained by SEM, HR-TEM, XRD, UV-VIS spectroscopy and the BET technique. The effects of various operational parameters such as substrate/H2O2 molar ratio, reaction temperature, catalyst concentration and solvent effect on the hydroxylation of anisole have been studied in detail. The microporous TS-1 catalyst showed 32% anisole conversion with 34% selectivity to PMP, while the micro/mesoporous DTS-1 catalyst showed enhanced activity for anisole hydroxylation, i.e. 54% conversion with 55% selectivity towards PMP. The increased framework Ti and improved accessibility of the active sites located in the channels of DTS-1, which permit the mass transfer of reactants, transition states and products from the mesopores of DTS-1, were responsible for the enhanced catalytic activity and selectivity towards p-methoxyphenol.

Direct conversion of N-acetyl-d-glucosamine to N-containing heterocyclic compounds 3-acetamidofuran and 3-acetamido-5-acetyl Furan - Shaikh, Samrin S.; Patil, Chetana R.; Lucas, Nishita; Bokade, Vijay V.; Rode, Chandrashekhar V. (Waste and Biomass Valorization, 2023)
Purpose Effectual waste utilization from plant as well as marine biomass has gained tremendous importance with reference to sustainability. The valorization of marine biomass produces value added compounds containing not only C, H, O but also renewable N atom in the skeleton which widens the scope for its exploration which may prove to be economically beneficial to the society. Heterogeneous catalytic transformation of marine biomass i.e. N-acetyl glucosamine (NAG) to N-substituted aromatic heterocyclic furan derivatives is reported for the very first time. Cost effective and stable metal oxide catalysts were deployed for the transformation. Catalyst screening study showed that La2O3 was found to be an excellent catalyst for N-acetyl glucosamine (NAG) dehydration which mainly produced 3-acetamidofuran (3AF). Methods The physicochemical properties of the metal oxide catalyst were investigated by various techniques such as XRD, FTIR, MeOH-FTIR, TPD, SEM, N-2 sorption studies and HR-TEM analysis for structure activity relationship. Results The effect of various reaction parameters such as catalyst concentration, reaction temperature, reaction time and solvent effect on dehydration of N-acetyl glucosamine has been studied in detail for higher yields. The results revealed that the presence of weak basic sites which are Bronsted in nature and nano pores present on the surface were responsible for improved dehydration of the chitin biomass to selectively yield 3-acetamidofuran (3AF). La2O3 catalyst showed optimum 50% 3AF yield from N-acetyl glucosamine at 180 degrees C in 3 h. Conclusion Efficacious exploitation of marine biomass to value added chemicals using heterogeneous catalysts can be extensively exploited. Separation of N-substituted heterocyclic aromatics is the most innovative aspect of the current study. Thus, utilization of heterogeneous catalyst and renewable biomass as a raw material indicates a transition towards more sustainable and greener approach.{GRAPHICAL ABSTRACT
Keywords: 3-acetamido-5-acetylfuran; 3-acetamidofuran; dehydration; heterogeneous catalysis; Lanthanum oxide; N-acetyl-D-glucosamine; renewable feedstock